A survey on the under utilization of the abbreviated dialing and the 3-party call facilities at Telekom Malaysia's Batu Pahat 2nd exchange - Ariffin, Mohd. Sofi (1993)
The survey was done in the TM's Batu Pahat Second Exchange coverage area, on August 25tn to September 15th , 1993. The research was carried out because the researcher found that there was several facilities in the Enhanced Telephone Facilities were under utilization. The Abbreviated Dialing and 3-Party Call Facilities were the among these under utilized facilities. The objective of this research were to identify; the reasons why there was lack of TM's residential customers subscribed the Abbreviated Dialing and 3-Party Call Facilities in Batu Pahat second exchange coverage area; whether the non subscribers of the facilities will subscribe in the future; and a causal relationships with the factors such as, knowledge, monetary, need and want, and perception on the post-purchase satisfaction. The mail and personal interview had been used as the data collection techniques. One hundred filled questionnaires were collected using these techniques. The mail interview was contributed 15 filled questionnaires, while from the personal interview 85 questionnaires were collected. Therefore, the total was 100 filled questionnaires. One hundred respondents, as a sample size, had been chosen from the 12,298 population by using the non probability sample selection. The researcher used a convenience sampling selection in selecting the respondents. One assumption had been made in carrying this research which is, "the customers should aware of the facilities existence before they subscribed the facilities".